PANORAMA GERAL DOS PROGRAMAS DE TRANSFERÊNCIA DE RENDA NA AMÉRICA LATINA E CARIBE - Maria Ozanira da Silva e Silva (Revista de Políticas Públicas, 2014)
The article, based on a survey, has as objective to contextualize and to draft a general view about the Conditioned Income Transfer Programs (PTRC) in implementation in Latin America and Caribbean. In order to develop a general problematization about those programs, it was pointed out its main traces, highlighting its structural contribution and weakness to meet the central objective that is to fight poverty and extreme poverty. The search of information was in the sites and some documents, allowing stand out the importance of those programs in the field of the non contributive social protection in the ambit of the social policies in the Continent.